Analisis Kesalahan Siswa Dalam Menyelesaikan Permasalahan Matematika Menurut Teori Polya Ditinjau dari Kecemasan Matematika - Rizal Fahmi Himawan (Program Studi S1 Matematika UNESA, 2021)
Mathematical anxiety is a feeling of panic, helplessness, stiffness, paralysis, and mental disorders that arise in a person when they are asked to solve a mathematical problem thoroughly in everyday life or in academic situations. Mathematical anxiety can have a negative effect on learning ability, application skills, and problem solving abilities. The use of uncommon mathematical problems can encourage the development of critical, creative thinking skills and higher order thinking skills from these students. The purpose of this study was to analyze the types of errors made by VIII grade Junior High School student in solving a problem with Pythagorean material based on Polya's theory with a high level of mathematical anxiety and a low level of mathematical anxiety. This research is a descriptive study using a qualitative approach. Sources of data in this study were 2 VIII grade Junior High School student even semester. There are 3 instruments in this research, namely: mathematics anxiety scale questionnaire, mathematics problem solving test, and interview guide. In this study, the mathematics anxiety scale used was an anxiety scale that was adapted from a scale developed by Mahmood and Khatoon (2011) which was obtained from an adaptation of the Mathematics Anxiety Scale questionnaire. Math problem solving tests are used to find out where students' mistakes are in the process of solving mathematical problems. Interviews are used to find out the reasons and factors that cause students to make mistakes in the process of solving mathematical problems. The results showed that: 1. Grade VIII junior high school students with a high level of mathematics anxiety made mistakes in procedural mistake category in the stages of making plans stage, executing plans stage, and re-checking stage. 2. Grade VIII junior high school students with low mathematical anxiety level made mistakes in conceptual mistake category in the re-checking stage.